2013
DOI: 10.1177/0300060513502887
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of 18F-fluorodeoxyglucose positron emission tomography/computed tomography and magnetic resonance imaging in early diagnosis of vulnerable carotid atherosclerotic plaques

Abstract: Thin or ruptured plaques, lipid-rich plaques and haemorrhagic plaques possess high inflammatory activity. The combination of (18)F-FDG PET/CT and MRI could be useful for qualitative and quantitative diagnosis of carotid atherosclerotic plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In 18 patients with cryptogenic stroke and non-stenosing carotid atheroma, the presence and size of MRI-measured lipid core in ipsilateral carotid plaque were associated with FDG uptake ( 12 ). Similar findings were reported in a Chinese MRI/PET study of asymptomatic patients with non-stenosing carotid plaque ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In 18 patients with cryptogenic stroke and non-stenosing carotid atheroma, the presence and size of MRI-measured lipid core in ipsilateral carotid plaque were associated with FDG uptake ( 12 ). Similar findings were reported in a Chinese MRI/PET study of asymptomatic patients with non-stenosing carotid plaque ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…Few data exist relating other MRI morphological features with FDG uptake. Inverse associations were observed between FDG uptake and ipsilateral carotid plaque fibrous cap thickness in patients with cryptogenic stroke and non-stenosing plaque, and in asymptomatic Chinese patients thicker caps and calcification were associated with lower FDG uptake ( 12 , 13 ). We found no association between FDG uptake and IPH, unlike 2 earlier studies that reported positive associations ( 12 , 14 ).…”
Section: Discussionmentioning
confidence: 91%
“…Thin or ruptured, lipid-rich, and hemorrhagic plaques have high inflammatory activity, which manifests as high FDG uptake at imaging (85). Increased FDG uptake seen in carotid plaques (Fig 9) has been shown to be a predictive factor in plaque rupture (86) and ischemic events.…”
Section: Soft-tissue Necrosis and Granulation Tissue-mentioning
confidence: 98%
“…21) A study compared FDG-PET with MRI findings and indicated that the TBR was high at the sites of plaque with a ruptured fibrous cap, lipid-rich plaque, and intra-plaque hemorrhage. 22) Furthermore, another study compared FDG-PET with carotid CT and reported that the presence or absence of three factors (positive remodeling, irregular lumen, and low attenuation) characterizing vulnerable plaque on CT, as well as the number of factors, were correlated with FDG accumulation. 23)…”
Section: Fdg-pet For Arteriosclerosis and Carotid Artery Lesionsmentioning
confidence: 99%